Privacy-preserving healthcare data management system using blockchain technology - Arshad, Abir; Das, Devamitra; Rahman, Md.Mostafizur; Mostafi, Md.Tarik-Ul-; Biswas, Swapnil (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.